SIMULATION OF AN ENGINE FRICTION STRIP TEST - Krishnan, Akhil (My University, 2014)
Over the years, internal combustion engine technology development has been targeted towards improving operating efficiency and thereby lowering fuel consumption. Friction Mean Effective Pressure (FMEP) accounts for 7-15% of the total indicative power produced in an engine cycle for large diesel engines, such as in trucks. The base-engine components such as piston rings, bearings, gears, seals and pumps contribute 60% - 70% of this FMEP. Minimizing the friction losses in the engine would translate to a direct reduction in fuel consumption. The development of low friction engine technology requires extensive studies and testing, with major challenges associated with the accurate measurement of individual component contribution to the overall engine friction power loss. Therefore, the requirement for a ‘Virtual Engine Friction Strip Test’ using modern simulation tools is exigent. This thesis project, in association with the Tribology and Mechanics research group, at the Advanced Technology and Research department at Volvo Group Trucks Technology aims at developing a full engine strip down test simulation model. Owing to the large number of active components on an engine contributing to the overall friction losses, the scope of this study is restricted to the major friction contributors in the cranktrain – piston rings, skirts, journal bearings on the connecting rods and the main crankshaft journal bearings. A one-dimensional analytical model was prepared using the Gamma Technologies’ GT-Suite simulation tool. The dynamics of the crankshaft and the piston cylinder unit are modeled. The hydrodynamics of the lubrication films for the bearings, rings and skirts are solved quasi-statically, and mixed lubrication and asperity contact lubrication are also modeled. Combined with an oil thermal model, a shear thinning model, and accurate measurement data, a detailed insight of the engine friction can be obtained. The model was validated against various other simulation approaches and against strip tests of the Volvo MD13 Euro 4 DST Engine. The same test conditions of the strip tests are reproduced on the simulation model, and the results are compared. In order to establish the model fidelity and robust solution methodology, it is also used to perform various studies on friction reduction techniques. This Virtual Engine Strip Test simulation model provides an opportunity to analyze new friction reduction methods and unconventional engine designs, towards the development of a low friction engine.
Keywords: Transport; Hållbar utveckling; Farkostteknik; Transport; Sustainable Development; Vehicle Engineering